Endoscopic Flexor Hallucis Longus Tendon Transfer for the Management of Chronic Achilles Tendon Ruptures: A Systematic Review - Lucy Harriss; Freideriki Poutoglidou; Francesc Malagelada; Lucky Jeyaseelan; Amit Patel (Journal of Foot and Ankle Surgery (Asia Pacific))
Aim and background: Endoscopic flexor hallucis longus (FHL) transfer is a minimally invasive alternative technique for managing chronic Achilles tendon ruptures (CATRs) with large defects. This systematic review aims to investigate the clinical outcomes and complications associated with this technique in patients with CATRs. Methods: PubMed, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for relevant studies from their inception up to July 2024. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed. The studies were assessed for risk of bias using the National Heart, Lung, and Blood Institute (NHLBI) critical appraisal checklist. Data extracted from each study included population characteristics, surgical technique, clinical outcomes, and complications. Results: Ten studies with a total of 71 patients were included in the review. According to the NHLBI checklist, two studies were rated as good quality, three studies as fair quality, and five studies as poor quality. Clinical assessments primarily used the single heel raise test (SHRT), the American Orthopedic Foot and Ankle Scoring System (AOFAS), and the Achilles Tendon Total Rupture Score (ATRS), along with the Victorian Institute of Sports Assessment-Achilles (VISA-A), the American Orthopedic Foot and Ankle Society Ankle-Hindfoot Score (AAOS), and subjective assessments of pain and shoe comfort. Functional scores improved across all studies. Specifically, AOFAS increased from 54.02 preoperatively to 93.90 postoperatively in three studies, while ATRS improved from 22.38 preoperatively to 95.51 postoperatively in two studies. The overall failure rate was 0% with no requirement for revision or augmentation. The overall complication rate was 14.1% with no major complications reported. Minor complications included one operative complication and six functional complications: ectopic bone formation at the screw site (n = 1), ankle joint stiffness (n = 1), moderate pain (n = 3), and moderate footwear discomfort (n = 2). Neurovascular complications involved temporary changes in sensation (n = 2). Conclusion: Endoscopic FHL transfer is an effective technique for treating CATRs, demonstrating good functional outcomes and limited complications. However, data interpretation is constrained by the absence of high-level evidence in the literature. Currently, there are no well-designed randomized controlled trials in the literature comparing the outcomes of the technique with those of open surgery, which limits the broader application of these findings in clinical practice. Future research should focus on addressing this gap.